SODIUM BREAD OF FRUITS ON WHITE BACKGROUND (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the author approached from the point of view of the latest achievements in the science of "Rangtasvir" for the 2nd-level undergraduate students of the "Fine Arts and Engineering Graphics" field of study. Teaching the science of painting, explaining it step by step to students is the most difficult process. Therefore, the scientific-theoretical and practical-methodical foundations of this science are enriching their features year by year. In the article, serious attention is paid to the theoretical and methodological foundations of the science of "Rangtasvir", its content, function, components, their tasks, secrets, techniques, representation of the picture, stages of drawing, and the history of the creation of rare works. At the same time, special attention is paid to the methodology of teaching color and image science. most of the drawings presented in the article are developed by the author and are fully covered technically. In the article, students of the 2nd level of fine arts and engineering graphics will learn the science of painting and how to express pictures and compositions, proportions, proportion, color harmony, horizon.